PEMANFAATAN LAMPU PERANGKAP UNTUK MENGENDALIKAN POPULASI ULAT BAWANG, Spodoptera exigua HUBNER (Lepidoptera : Noctuidae) PADA PERTANAMAN BAWANG MERAH - Ahdin - Gassa; Fatahuddin Fatahuddin; Muslimin Sepe (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2023)
Since ancient times, leeks (Allium cepa L.) have been widely cultivated and consumed by people around the world, the cultivation of shallot plants cannot be separated from the problem of plant disrupting organisms, especially Spodoptera exigua pests. The purpose of this study was to measure the effectiveness of trap lights on the intensity of S. exigua attacks on onion plants. This study is a field experiment that compares two types of trap lamp treatment, namely yellow and blue trap lights, to the intensity of S. exigua pest attacks on onion plants. The results showed that the average intensity of S. exigua attacks on yellow trap light treatment was lower (10.63%) than blue trap lamp treatment (11.05%). The total production of shallot wet bulbs in the yellow light trap treatment was around 4.66 tons/ha lower than the blue light trap of 6.86 tons/ha. Analysis of the T test of both treatments showed markedly different results only in observations of 7 and 23 days after planting.